Road, The - Coates, Austin (Echoes (Hong Kong, China), 2009)
Set in 1950s Hong Kong, The road paints an evocative picture of comfortable colonial life, while at the same time presenting the local people with the shrewd understanding that the author had acquired as District Officer in rural Hong Kong.